PERANCANGAN SISTEM INFORMASI PERMINTAAN BARANG ATK BERBASIS WEB PADA BADAN PENDAPATAN DAERAH KOTA TANGERANG - Eka Wulansari Fridayanthie (LPPM Universitas Bina Sarana Informatika, 2018)
Procurement of ATK Goods can be implemented effectively and efficiently with the principles of healthy, transparent, open, and fair trade practices for all parties. Procurement of Goods Government is an activity to obtain goods Unit Unit Region / Other institutions whose process starts from the planning needs until the completion of it all its activities to obtain goods. Along with the development of the increasingly modern darana and government infrastructure also varied following developments and tailored to the needs of the government. The procurement of goods is financed by the State / Regional Budget. The results of this study include the procurement of goods in the Regional Revenue Board in general has been in accordance with the system and mechanisms specified in the rules. However, after being reviewed and reviewed more deeply there are still some constraints and fraudulent behavior committed by the procurement committee and procurement participants and the parties involved in the procurement process of the goods.